2005
DOI: 10.1016/j.femsyr.2004.11.004
|View full text |Cite
|
Sign up to set email alerts
|

-mediated expression in

Abstract: The b-Zip transcription factor Yap1p plays an important role in oxidative stress response and multidrug resistance in Saccharomyces cerevisiae. We have previously demonstrated that the KNQ1 gene, encoding a multidrug transporter of the major facilitator superfamily in Kluyveromyces lactis and containing two potential Yap1p response elements in its promoter, is a putative transcriptional target of KlYap1p, the structural and functional homologue of ScYap1p. In this work, we provide evidence that KlYAP1 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, phylogenetic analyses of the DHA1 and DHA2 subfamilies in other hemiascomycete yeasts have identified several functionally characterized transporters presumably involved in the MDR/MXR phenomenon (Gbelska et al, 2006; Dias et al, 2010; Dias and Sa-Correia, 2013). These include CgTpo3, which plays a role in polyamine homeostasis and azole drug resistance (Costa et al, 2014), mirroring its S. cerevisiae homolog Tpo3; Nag3, and Nag4, which catalyze the uptake of N-acetylglucosamine in Candida albicans and are also involved in drug sensitivity and virulence (Yamada-Okabe and Yamada-Okabe, 2002; Sengupta and Datta, 2003; Wendland et al, 2009); Ffz1 and Ffz2, two characterized importers of fructose in Zygosaccharomyces rouxii (Leandro et al, 2011) (and Z. bailli for Ffz1, Pina et al, 2004) with no known role in MDR/MXR; and Knq1, a Kluyveromyces lactis transporter that is involved in iron homeostasis, drug resistance and oxidative stress response under the control of KlYap1 (Takacova et al, 2004; Imrichova et al, 2005; Marchi et al, 2007), the K. lactis homolog of S. cerevisiae 's Yap1. Interestingly, although KNQ1 shares some sequence identity with ATR1 , there is no close homolog in S. cerevisiae , with the exception of S. cerevisiae JAY-291, a fully sequenced strain that is widely used in bioethanol production (Argueso et al, 2009).…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%
“…Interestingly, phylogenetic analyses of the DHA1 and DHA2 subfamilies in other hemiascomycete yeasts have identified several functionally characterized transporters presumably involved in the MDR/MXR phenomenon (Gbelska et al, 2006; Dias et al, 2010; Dias and Sa-Correia, 2013). These include CgTpo3, which plays a role in polyamine homeostasis and azole drug resistance (Costa et al, 2014), mirroring its S. cerevisiae homolog Tpo3; Nag3, and Nag4, which catalyze the uptake of N-acetylglucosamine in Candida albicans and are also involved in drug sensitivity and virulence (Yamada-Okabe and Yamada-Okabe, 2002; Sengupta and Datta, 2003; Wendland et al, 2009); Ffz1 and Ffz2, two characterized importers of fructose in Zygosaccharomyces rouxii (Leandro et al, 2011) (and Z. bailli for Ffz1, Pina et al, 2004) with no known role in MDR/MXR; and Knq1, a Kluyveromyces lactis transporter that is involved in iron homeostasis, drug resistance and oxidative stress response under the control of KlYap1 (Takacova et al, 2004; Imrichova et al, 2005; Marchi et al, 2007), the K. lactis homolog of S. cerevisiae 's Yap1. Interestingly, although KNQ1 shares some sequence identity with ATR1 , there is no close homolog in S. cerevisiae , with the exception of S. cerevisiae JAY-291, a fully sequenced strain that is widely used in bioethanol production (Argueso et al, 2009).…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%
“…We have previously demonstrated that the KNQ1 gene, the structural and functional ortholog of the ScATR1 gene encoding a multidrug transporter of the MFS in K. lactis, is a transcription target of KlYap1p (Takacova et al 2004). The H 2 O 2 and diamide-induced transcriptional activation of KNQ1 is fully dependent on KlYap1p (Imrichova et al 2005). As Fig.…”
mentioning
confidence: 70%
“…The media were solidified with 2% bactoagar. The KlPDR1 and KlYAP1 genes (Imrichova et al 2005;Balkova et al 2009) were cloned in multicopy plasmid pRS306K (2 µm URA3 ARS1 KARS2 ori Amp r ) (Heus et al 1994) under the control of their own promoter. Yeast cells were transformed by electroporation (Thompson et al 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, animals do not apparently share the same mechanism with fungi of a NOX-mediated increase of ROS triggered by excess NADPH. The homologs of AnCF and NapA are highly conserved in many filamentous fungi and yeasts, including most of the Aspergillus species (Brakhage et al 1999 ; Zheng et al 2015 ; Hortschansky et al 2017 ; Mendoza-Martinez et al 2017 ), S. cerevisiae (McNabb et al 1995 ; Rodrigues-Pousada et al 2019 ), S. pombe (McNabb et al 1997 ; Boronat et al 2014 ), Kluyveromyces lactis (Mulder et al 1994 ; Imrichova et al 2005 ) and Cryptococcus neoformans (Loussert et al 2010 ; Pais et al 2016 ). While systematic studies remain lacking, the striking mechanistic similarities in ROS defense between A. nidulans and these fungi indicate that utilizing NADPH fluctuation to assure timely activation and avoid overactivation of the key antioxidants as an oxidative adaptation strategy may be conserved among these fungi.…”
Section: Discussionmentioning
confidence: 99%